3D-PTV Measuring onBubble and Liquid Velocities of a Single Bubble Jet - Katsuya HIRATA; Ryo KAWAGUCHI; Miki TAOKA; Jiro FUNAKI (Journal of Fluid Science and Technology, 2013)
This experimental research concerns a simple air-bubblejet from a bottom nozzle in water. We try to conduct the measurements of the flow by applying a three-dimensional particle tracking velocimetry (3D-PTV) technique, in order to specify both bubble (air) and liquid (water) velocities. As tracer particles, we regard bubbles themselves in bubble-velocity measurements, and polyethylene particles suspended in water in liquid-velocity measurements. Then, we visualise the three-dimensional motions of the bubbles and the liquid. As we record stereo images using a pair of high-speed video cameras, we can get temporally-consecutive spatial information of both the bubbles' and liquid's motions. As a result, we quantitatively reveal the three-dimensional and instantaneous behaviour of the unsteady bubble-jet flow. And, using the obtained three-dimensional information, we show the fundamental flow structure of the bubble jet from a statistical view point.